Determinants and outcomes of caesarean delivery: elective versus emergency in a tertiary care teaching institute in Kerala, India - T., Heera Shenoy; K., Remash; T., Sheela Shenoy (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: Globally, the caesarean delivery rate is rising continuously, making caesarean one of the most common surgical procedures. The purpose was to analyse the determinants and maternofoetal outcomes in elective versus emergency caesarean sections in a tertiary care centre. Methods: All women, who gave birth by Caesarean deliveries done over a period of 1 year (January 2018-December 2018), were studied in Travancore Medical College in Kerala, India. Indications of caesarean, whether emergency or elective, medical morbidities, Gestational age at decision, birthweights and extended hospital stay and new-borns needed to resuscitate were looked into. The data was collected and analysed from the hospital registry. Results: Out of the 378 selected patients, 95 patients in group of elective and 283 emergency caesarean section were studied. The indications of emergency caesarean sections were failed induction, non-progression of labour, CPD, Previous caesarean in labour, foetal distress. The most frequent indicator for elective lower segment caesarean section (LSCS) was patient with previous LSCS not willing for vaginal birth, followed by breech presentation and high risk pregnancy ( BOH and ART). Younger mothers, gestational age remote from term, low-birth weight, and extended hospital stay were statistically significant in mothers undergoing emergency caesarean delivery. Fever, urinary tract infections, need for maternal and neonatal ventilation, blood transfusion, scar dehiscence were more common in the emergency caesarean group. Conclusions: The antenatal morbidity, low birth weights, decision taken preterm for salvaging the baby, postoperative complications and extended stay were more in the emergency caesarean when compared to elective caesarean.